Effect of supplementation of area specific mineral mixture on reproductive performance of the cows - MOHAPATRA, P; SWAIN, R K; MISHRA, S K; SAHOO, G; ROUT, K K (The Indian Journal of Animal Sciences, 2012)
Sample of feeds and fodders and serum of cows were collected for mineral analysis. An on-farm trial was carried out in which 80 cows having reproductive disorders were allotted to 4 groups with 20 animals — G1 (control); G2 20 an oestrous heifers supplemented with area specific mineral mixture (ASMM) @ 50 g/day/animal (ANH); G3, 20 anoestrous cows supplemented with ASMM @ 50 g/day/animal (ANC); and G4, 20 repeat breeding cows supplemented with ASMM @ 50 g/day/animal (RBC). In cows, the mean serum Ca and P levels were lower while the mean Zn, Cu, Mn and Fe were higher than critical level. At the end of experimental feeding, the body weights, metabolic body weights, dry matter intake per kg metabolic body weight, DCP and TDN intake of the animals did not differ significantly. The overall serum mineral levels and biochemical values increased significantly in supplemented group than in un-supplemented group. The percentage conception was 5, 40, 40 and 35 in G1, G2, G3 and G4 groups, respectively. Services per conception were significantly lower in the mineral supplemented group than control. Similarly the post-partum oestrous was significantly lower in G2 and G3 cows compared to control animals. Thus the reproductive performance improved due to supplementation of area specific mineral mixture.